Effective Enrichment and Mass Spectrometry Analysis of Phosphopeptides Using Mesoporous Metal Oxide Nanomaterials - Nelson, Cory A. (2010)
Mass spectrometry (MS)-based phosphoproteomics remains challenging due to the low abundance of phosphoproteins and substoichiometric phosphorylation. This demands better methods to effectively enrich phosphoproteins/peptides prior to MS analysis. We have previously communicated the first use of mesoporous zirconium oxide (ZrO(2)) nanomaterials for effective phosphopeptide enrichment. Here we present the full report including the synthesis, characterization, and application of mesoporous titanium dioxide (TiO(2)), ZrO(2), and hafnium oxide (HfO(2)) in phosphopeptide enrichment and MS analysis. Mesoporous ZrO(2) and HfO(2) are demonstrated to be superior to TiO(2) for phosphopeptide enrichment from a complex mixture with high specificity (>99%), which could almost be considered as “a purification”, mainly because of the extremely large active surface area of mesoporous nanomaterials. A single enrichment and Fourier transform MS analysis of phosphopeptides digested from a complex mixture containing 7% of α-casein identified 21 out of 22 phosphorylation sites for α-casein. Moreover, the mesoporous ZrO(2) and HfO(2) can be reused after a simple solution regeneration procedure with comparable enrichment performance to that of fresh materials. Mesoporous ZrO(2) and HfO(2) nanomaterials hold great promise for applications in MS-based phosphoproteomics.